2004
DOI: 10.1007/s00440-004-0369-4
|View full text |Cite
|
Sign up to set email alerts
|

Glauber dynamics on trees and hyperbolic graphs

Abstract: We study continuous time Glauber dynamics for random configurations with local constraints (e.g. proper coloring, Ising and Potts models) on finite graphs with n vertices and of bounded degree. We show that the relaxation time (defined as the reciprocal of the spectral gap |λ 1 − λ 2 |) for the dynamics on trees and on planar hyperbolic graphs, is polynomial in n. For these hyperbolic graphs, this yields a general polynomial sampling algorithm for random configurations. We then show that for general graphs, if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
231
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 140 publications
(241 citation statements)
references
References 34 publications
(59 reference statements)
10
231
0
Order By: Relevance
“…This is the content of our first main result; in fact, we are able to prove that the mixing time is Ç´Ò ÐÓ Òµ, which is optimal: This analysis has several advantages over previous ones [4,36]: it is more direct, applies also when there is an external field, gives a technically stronger result (as explained below), and applies to models more general than the Ising model. We now proceed to sketch some of our techniques and point out the main technical innovations.…”
Section: Main Results and Techniquessupporting
confidence: 53%
See 4 more Smart Citations
“…This is the content of our first main result; in fact, we are able to prove that the mixing time is Ç´Ò ÐÓ Òµ, which is optimal: This analysis has several advantages over previous ones [4,36]: it is more direct, applies also when there is an external field, gives a technically stronger result (as explained below), and applies to models more general than the Ising model. We now proceed to sketch some of our techniques and point out the main technical innovations.…”
Section: Main Results and Techniquessupporting
confidence: 53%
“…The Glauber dynamics for the Ising model on trees has also been studied. In a recent paper [4], it is shown that the mixing time with a free boundary on a complete -ary tree with Ò vertices is Ç´Ò ÐÓ Òµ at high and intermediate temperatures (i.e., when ¬ ¬ ½ ) Ý . Moreover, as soon as ¬ ¬ ½ the mixing time becomes Ò ½·ª´½µ , and the exponent is unbounded as ¬ ½.…”
Section: The Ising Model On Treesmentioning
confidence: 99%
See 3 more Smart Citations